Compensatory inter vivos gifts - Stefan Hochguertel; Henry Ohlsson (Levy Economics Institute of Bard College, 2000)
Empirical studies of intergenerational transfers usually find that bequests are equally divided among heirs while inter vivos gifts tend to be compensatory. Using the 1992 and 1994 waves of the Health and Retirement Study, we find that only 4 percent of parents who give divide their gifts equally among their children. Estimating probit models using family panels, we find that gifts are compensatory in the sense that a child is more likely to receive a gift if she works fewer hours and has lower income than her brothers and sisters; these results carry over to the amounts given. Fixed effects Tobit estimations show that the fewer hours a child works and the lower her income is, the more the parents give. These results imply that gifts are compensatory. The empirical results are, therefore, consistent with the predictions of the altruistic model of intergenerational transfers.
Keywords: 330